DISIPLIN PEGAWAI NEGERI SIPIL MELALUI SISTEM PENGAWASAN BERBASIS APLIKASI SIAP KERJA DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BANJARNEGARA - Zenny Putri Zulfania; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
This study aims to analyze the influence of the SIAP Kerja application-based supervision system on the level of discipline of Civil Servants at the Secretariat of the Regional People's Representative Council of Banjarnegara Regency and identify supporting and inhibiting factors in its implementation. This study uses a mixed method with the Sequential Explanatory type by distributing questionnaires to 24 Civil Servants and continued with interviews and documentation to deepen the quantitative results. Data analysis uses simple linear regression. The results show that supervision through the SIAP Kerja application and employee discipline are both in the very good category with an average score of 4.48% and 4.42%, respectively. Statistically, a significance value of 0.000 < 0.05 and t count (8.340) > t table (2.074) is obtained, which indicates a significant influence. The coefficient of determination value of 0.760 indicates that 76% of employee discipline variations are influenced by the supervision system, while 24% are influenced by other factors. Qualitative findings indicate that the system is more transparent, objective, and integrated with the TPP and e-Kinerja, thus improving compliance with working hours. Despite technical challenges such as network disruptions and potential GPS manipulation, the SIAP Kerja application is generally effective in improving employee discipline.